Performance characterization of a microwave transistor subject to the noise and matching requirements - Gunes, Filiz; Demirel, Salih (WILEY, 2016)
In this paper, the gain G(T) of a microwave transistor is expressed analytically in terms of the mismatchings (V-in >= 1, V-out >= 1) at the ports, noise figure F >= F-min and the [z]-parameter and noise parameters. Firstly, because the input termination Z(S) determines the noise F >= F-min, thus the input termination Z(S) is pre-determined to lie on the tangent constant noise and available gain circles so that the maximum power delivery is ensured for the given noise. Then, a design configuration is constructed in the input impedance Z(in)- plane covering the gain and the required input and output mismatch circles within the Unconditionally Stable Working Area for the predetermined input termination Z(S). Finally, the compatible (F >= F-min, G(T), V-in >= 1, V-out >= 1) quadrates for either required or optimum (V-in >= 1, V-out >= 1) couples are obtained with their (Z(S), Z(L)) couples from the analysis of the design configuration. Furthermore, a case study is also presented for the full flexible performance characterization of a selected microwave transistor. It can be concluded that the near future microwave transistor is expected to be identified by performance data base built by its compatible (F >= F-min, G(T), V-in >= 1, V-out >= 1) quadrates and the (Z(S), Z(L)) terminations within the device operation domain to overview all the possible low-noise amplifier designs using the full device capacity. Copyright (C) 2015 John Wiley & Sons, Ltd.
Keywords: microwave transistor; transducer gain; noise figure; input VSWR; output VSWR; unconditional stability; conditional stability; AMPLIFIER; DESIGN; POWER; FEEDBACK; MODEL; CIRCLES; FIGURE; Engineering